Pengaruh Partisipasi Penyusunan Anggaran Dan Komitmen Organisasi Terhadap Kinerja Manajerial Dengan Variabel Intervening Budaya Organisasi Pada Pemerintah Kabupaten Bondowoso - Elviera Mayarani; Sri Wahyu Lelly Hana Setyanti; Hari Sukarno (ITB AAS INDONESIA, 2021)
This study aims to discuss the Effect of Budgeting Participation and Organizational Commitment on Managerial Performance with Organizational Culture Intervening Variables in Bondowoso Regency Government. This research was conducted to examine the factors that can support managerial performance in budgeting. The focus of this research is on the Bondowoso district government by using a sampling technique that is carried out using a questionnaire. This type of research uses a quantitative descriptive method with a theoretical study of the factors that affect managerial performance. The results of this study indicate that: 1) Budgeting Participation has an effect on Managerial Performance in Bondowoso Regency Regional Apparatus Organizations (OPD), 2) Budgetary Participation has an effect on Organizational Culture of personnel in Bondowoso Regency Regional Apparatus Organizations (OPD), 3) Organizational Committees have an effect on on Managerial Performance in Regional Apparatus Organizations (OPD) Bondowoso Regency, 4) Organizational Committees affect the Organizational Culture of personnel in Bondowoso Regency Regional Apparatus Organizations (OPD), 5) Organizational Culture affects Managerial Performance in Bondowoso Regency Regional Apparatus Organizations (OPD).